Comparative biomechanical analysis of hurdle clearance techniques on 110 m running with hurdles of elite and non-elite athlete - Bubanj, R.; Stankovic, R.; Rakovic, A.; Bubanj, S.; Petrovic, V.; Mladenovic, D. (Serbian Journal of Sports Sciences, 2008)
The purpose of this scientific work was to compare the differences in the hurdle clearance techniques and speed between elite athletes achieving top results and physical education students. The comparison of the hurdle clearance technique was made on the basis of the biomechanical models of Colin Jackson and Darko Mladenovic. Biomechanical model of Colin Jackson was taken from "Application of biomechanics in track and field" [11]. Analysis of the biomechanical model of Darko Mladenovic was made at the Faculty of Physical Education in Niš. By comparing those results we could conclude that there were considerable differences in the speed of hurdle clearance while the difference in the technique of hurdle clearance was significantly smaller. This research could also conclude that for the top results to be achieved a great speed of hurdle clearance is essential.